Term of Reference on Politeness of Speech in Manado Malay - Grace Shirley Luntungan (AIBPM Publisher, 2020)
This research aims to explore and explain the “term of reference” on politeness of speech in Manado Malay. The methodology used is a descriptive exploratory method with a technique of tap, speaking and listening, free speaking engagement, record, and notes. The data analysis technique used is the determining element. Term of Reference (the form of referring someone as a reference) as a form of politeness in Manado Malay appears in the oral communication event, how greeting (ego) to the speech partner. These greetings forms are distinguishable in hierarchical relations and egalitarian relations. In general, speakers use the first-person pronoun kita with a variety of kits and atik, self-names (nick name), profession/ position names, term of kinship for the ego.